The Effectiveness of Input-Output Model-Based Political Education: An Empirical Study of First-Time Voters in Magelang City - Nyosisca Listyanti; Daru Murti Raharjo; Muhammad Fadhlullah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The participation of first-time voters serves as a critical benchmark for democratic regeneration. However, evaluations of political education programs organized by government agencies, such as the National Unity and Politics Agency (Kesbangpol), often focus on administrative compliance rather than substantive impact. This study aims to evaluate the effectiveness of political education programs in Magelang City using a systems approach (Input-Output Model). Employing a quantitative explanatory survey method, this research involved 49 high school/vocational students selected through purposive sampling. Data were analyzed using Multiple Linear Regression to examine the influence of Input dimensions (resources and facilities) and Output dimensions (comprehension and intention) on Political Participation Interest. Statistical analysis revealed an intriguing anomaly: the Input dimension showed no significant effect (\bm{p > 0.05}), whereas the Output dimension demonstrated a positive and significant influence (\bm{p < 0.05}). Simultaneously, both variables significantly affected participation interest. These findings indicate that for Generation Z, physical facilities and formalities function merely as "hygiene factors," while substantive understanding serves as the primary "motivator." This study recommends a policy reorientation from ceremonial approaches toward content-quality enhancement to effectively boost political engagement.